THE ROLE OF FINANCING ON BUSINESS DEVELOPMENT AND WELFARE IMPROVEMENT OF THE MEMBERS OF BAITUL MAAL WAT TAMWIL - Zulhazmi Zulhazmi; Ilmiawan Auwalin (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This research aims to determine the role of financing carried out by BMT UGT Sidogiri Wonokromo branch partially or simultaneously on the business development and improvement of the welfare of its members. The method used in this study is multiple regression analysis. The population used in this study were all members of the BMT UGT Sidogiri Wonokromo branch. This study used a sample of 35 people who were members of the BMG UGT Sidogiri Wonokromo branch, who met the sample criteria. The results of this study indicate that there is a simultaneous influence of financing on business development and the welfare improvement of its members in the BMT UGT Sidogiri Wonokromo branch. The results showed that partially the variables that had a significant effect on business development and welfare improvement were age, gender, total financing and the number of customers after participating in the financing.Keywords: financing, business development and welfare improvementREFFERENCE Ananda, F. (2011). Analisis perkembangan usaha mikro dan kecil setelah memperoleh pembiayaan mudharabah dari BMT At Taqwa Halmahera di Kota Semarang. Skripsi tidak diterbitkan. Semarang: Universitas Diponegoro.Al Farizi, M. (2015). Al-Qawa’id Al-Fiqhiyyah. Al Mabsut Jurnal Studi Islam dan Sosial, 9(2).Ansori, Muslich & Iswati, Sri. (2009). Buku ajar metodologi penelitian kuantitatif. Surabaya: Airlangga University Press.Chaudry, M. S. (2012). Sistem ekonomi Islam: Prinsip dasar. Edisi 1. Jakarta: Kencana.Fitriyaningsih, E. (2012). Pengaruh besar modal (modal sendiri), pemberian kredit, dan tingkat suku bunga kredit terhadap peningkatan pendapatan pedagang kecil di Desa Tirtonirmolo Kecamatan Kasihan Bantul. Skripsi tidak diterbitkan. Yogyakarta: Universitas Negeri Yogyakarta.Nurrohmah, I. (2015). Analisis perkembangan usaha mikro, kecil dan menengah sebelum dan sesudah menerima pembiayaan musyarakah pada koperasi jasa keuangan syariah BMT (Studi kasus: BMT Beringharjo Yogyakarta). Skripsi tidak diterbitkan. Yogyakarta: Universitas Negeri Yogyakarta.Rukminto Adi, Isbandi. (2005). Ilmu kesejahteraan sosial dan pekerjaan sosial. Depok: FISIP UI PRESS.Alcock, James & Sadava, Stan. (2014). An Introduction to social psychology global perspectives. New Delhi: Sage.Saputra, A. (2015). Pengaruh penyaluran pembiayaan BMT Bina Ihsanul Fikri (BIF) terhadap perkembangan usaha pedagang pasar tradisional di kota Yogyakarta. Skripsi tidak diterbitkan. Yogyakarta: Universitas Muhammadiyah Yogyakarta.Sriyatun. (2009). Analisis pengaruh pemberian pembiayaan mudharabah BMT terhadap peningkatan pendapatan pedagang kecil di Kabupaten Sukoharjo. Skripsi tidak diterbitkan. Surakarta: Universitas Muhammadiyah Surakarta.Supardi. (2005). Metodologi penelitian ekonomi dan bisnis. Yogyakarta: UII Press.